An Environment for Modeling and Managing the Process Design Process - Gonnet, Silvio Miguel (2001)
A three-layer object based environment architecture (Client, Application Server and Server) to support the modeling and management of the process design process is presented. It guides the design process and explicitly maintains the evolution of the design knowledge as a consequence of each design decision that is adopted during a particular design project. The Client encapsulates the interface of the designer to the design environment. The Application Server is responsible for managing the designer requirements by resorting to the Server data. It manages the definition of generic design tasks and the administration of the scenarios that are generated when a particular design process is carried out. Design tasks are defined according to the Coordinates language syntax. Basically, a design process is viewed as a set of tasks that are linked by temporal relationships and/or a set of resources they share. Generic design tasks can be instantiated and used in a specific design project. The Server contains the data that are created, used or modified by the Application Server.